Research, productivity, and output growth in Chinese agriculture - Fan, Shenggen; Pardey, Philip G. (Elsevier, 1997)
Recent attempts to quantify the sources of growth in Chinese agriculture have attributed an exceptionally large share of this growth to the contemporary institutional and market reforms within China. To analyze this important issue we use a newly constructed panel data set that includes an agricultural research or stock-of-knowledge variable. Our results suggest that while still a significant source of growth, the direct growth promoting consequence of institutional change and market reforms have been overstated by these earlier studies. Research-induced technical change accounts for a significant share (20%) of the growth in agricultural output since 1965.